A templating approach with phase change to tailored coordination of single- and multiple-atom catalysts - Zhong-Shuai Zhu; Pengtang Wang; Haobo Li; Ya Liu; Yunpeng Wang; Kunsheng Hu; Bernt Johannessen; Shiying Ren; Shuang Zhong; Hongqi Sun; Xiaoguang Duan; Shaobin Wang (Nature Communications)
Abstract Single-atom catalysts (SACs) with featured active sites exhibit exceptional catalytic activity and selectivity in catalysis. However, their scalable synthesis and precise control of structure coordination for on-demand atomic configurations remain the bottlenecks in practical applications. In this work, a facile and scalable strategy is developed to achieve massive production of varying molecular-coordinated single- and multi metal-based SACs. Low-cost NaCl is used as a recyclable and green template. Its nature of temperature-induced confinement with a phase change of ion dissociation can direct 3D honeycomb-like morphology of SACs with different coordinations of in-plane M–Nx (x = 4 or 6) at lower temperature and axial M–Cl at above melting point of NaCl (900 °C), as demonstrated by controlled experiments and theoretical computations. A library of 25 distinct SACs and high-entropy SACs containing five metals with tailored structure are synthesized in a mass yield ranging from 18.3% to 50.9%. More importantly, these SACs exhibit remarkable performance in catalytic oxidation of aqueous organics and electrocatalytic nitrate, carbon dioxide, oxygen reduction reactions, highlighting their promising potential for environmental remediation and energy applications.